2018
DOI: 10.1136/bmj.k4864
|View full text |Cite
|
Sign up to set email alerts
|

Measured energy content of frequently purchased restaurant meals: multi-country cross sectional study

Abstract: ObjectiveTo measure the energy content of frequently ordered meals from full service and fast food restaurants in five countries and compare values with US data.DesignCross sectional survey.Setting223 meals from 111 randomly selected full service and fast food restaurants serving popular cuisines in Brazil, China, Finland, Ghana, and India were the primary sampling unit; 10 meals from five worksite canteens were also studied in Finland. The observational unit was frequently ordered meals in selected restaurant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 45 publications
2
41
0
2
Order By: Relevance
“…The average energy content of main meals served in both fast food and full service restaurants exceed public health recommendations (i.e. 600 kcal or less for main lunch/dinner meals) [12,13]. In addition, consumers tend to underestimate the energy, fat and sodium content of meals when eating outside the home [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The average energy content of main meals served in both fast food and full service restaurants exceed public health recommendations (i.e. 600 kcal or less for main lunch/dinner meals) [12,13]. In addition, consumers tend to underestimate the energy, fat and sodium content of meals when eating outside the home [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Robinson and colleagues (doi:10.1136/bmj.k4982) and Roberts and colleagues (doi:10.1136/bmj.k4864) both conducted surveys of the energy content of main meal dishes served by full service and fast food restaurants 89. In the United Kingdom, Robinson and colleagues report a mean energy content of 751 kcal in main meal dishes served by fast food chains, and 1033 kcal in dishes served by full service restaurant chains.…”
Section: Deep-pan Crisp and Evenmentioning
confidence: 99%
“…Fast-food consumption is positively correlated with obesity rates across countries (19,20) , yet few studies have compared the energy (21) and nutrient (22) content of fast-food offerings across countries. Roberts et al (21) selected 223 meals from 111 randomly selected restaurants in Brazil, China, Finland, Ghana and India and reported that high energy content in fast-food and full-service restaurant meals was widespread globally, with only meals in China having significantly lower energy content compared with those in the USA. Dunford et al (22) examined salt levels in menu items in several multinational fast-food chains across countries and observed differences in salt content across similar products in different countries.…”
mentioning
confidence: 99%